KOMPARASI KEMAMPUAN PENALARAN MATEMATIS MAHASISWA DITINJAU DARI GAYA KOGNITIF - Santosa, Farah Heniati; Negara, Habib Ratu Perwira; Indrawati; Bahri, Samsul; Samsuriadi (Jurnal Pemikiran dan Penelitian Pendidikan Matematika (JP3M), 2019)
This study aims to obtain a picture of the achievement of mathematical reasoning abilities of students who obtain PBL learning in terms of cognitive fields dependent and field independent. This research is a quasi-experiment involving 97 first semester students. Analysis of the study used one way ANAVA. The research instruments were cognitive style tests and mathematical reasoning abilities tests. The results of the study concluded that there are differences in students' mathematical reasoning abilities that have field dependent and field independent cognitive styles, that is, students with independent field cognitive styles have better mathematical reasoning abilities compared to students with field dependent cognitive styles.